Pengaruh Motivasi dan Budaya Kerja terhadap Kinerja Pegawai pada Kantor Camat Abab Kabupaten Pali - Emilya, Emilya; Hardiansyah, Hardiansyah; Hendrasmo, Ignasius (Journal of Law & Policy Review, 2023)
This article aims to examine how much influence motivation and work culture have on employee performance, both partially and jointly. The problem centers on the influence of work motivation and culture and its relationship to employee performance at the Abab sub-district office, Pali Regency. This research used a quantitative approach with 100 respondents selected through proportional stratified random sampling. Research instruments include questionnaires, observation and documentation. Data was collected through questionnaires, direct observation and documentation. Data analysis uses the F test (ANOVA) and t test (T-Test), with support from observation results, to test the stated hypothesis. The results of the research show that motivation has an influence of 3.7% on employee performance at the ABAB Subdistrict Office, Pali Regency. On the other hand, work culture has a more dominant influence, namely 98.3%, on employee performance in the office. Overall, motivation and work culture together have an influence of 98.3% on employee performance at the ABAB Subdistrict Office, Pali Regency